Differing roles of functional movement variability as experience increases in gymnastics - Busquets, A.; Marina, M.; Davids, K.; Angulo-Barroso, R. (Journal of Sports Science & Medicine, 2016)
Current theories, like Ecological Dynamics, propose that inter-trial movement variability is functional when acquiring or refining movement coordination. Here, we examined how age-based experience levels of gymnasts constrained differences in emergent movement pattern variability during task performance. Specifically, we investigated different roles of movement pattern variability when gymnasts in different age groups performed longswings on a high bar, capturing the range of experience from beginner to advanced status. We also investigated the functionality of the relationships between levels of inter-trial variability and longswing amplitude during performance. One-hundred and thirteen male gymnasts in five age groups were observed performing longswings (with three different experience levels: beginners, intermediates and advanced performers). Performance was evaluated by analysis of key events in coordination of longswing focused on the arm-trunk and trunk-thigh segmental relations. Results revealed that 10 of 18 inter-trial variability measures changed significantly as a function of increasing task experience. Four of ten variability measures conformed to a U-shaped function with age implying exploratory strategies amongst beginners and functional adaptive variability amongst advanced performers. Inter-trial variability of arm-trunk coordination variables (6 of 10) conformed to a \-shaped curve, as values were reduced to complete the longswings. Changes in coordination variability from beginner to intermediate status were largely restrictive, with only one variability measure related to exploration. Data revealed how inter-trial movement variability in gymnastics, relative to performance outcomes, needs careful interpretation, implying different roles as task experience changes.